Implementation of the Critical Chain Project Management (CCPM) Model for Improving Time and Cost in a Project for House Type 36 - Tolu Tamalika; Deri Maryadi; Azhari Azhari; Yules Pramona; Mukminatun Ardaisi (Penerbit Goodwood, 2024)
Purpose: This study was conducted on a housing project in Type 36 Housing using the Critical Chain Project Management (CCPM) approach. The objective of this research was to achieve a more effective project timeline and a more efficient total project cost. Methodology: By eliminating 50% of the safety time, the method minimizes the safe time to achieve a 50% probability of completion without additional safety time using Critical Chain Project Management or CCPM in this project. Results: This approach results in a reduction of the project completion time from the original 18 working days to 15 working days. Additionally, this implementation leads to cost savings, with the calculated daily cost amounting to Rp.10,907,170.03. Through the application of Critical Chain Project Management, a 4-day Feeding Buffer and an 11-day Project Buffer were established. As a result, the completion time for the Type 36 house construction is reduced to 15 days, which is 3 days shorter than the initial project schedule of 18. Conclusions: The use of the Critical Chain Project Management (CCPM) method in the Type 36 house construction project reduces the completion time from 18 days to 15 days, with a 4-day Feeding Buffer and an 11-day Project Buffer. The Cut & Paste method reduces 50% of safety time, preventing cost overruns. As a result, the daily project cost is Rp 10,907,170.03. Limitations: This analyzing just focus on critical process but not for opportunity job can be reduce for more improvement. And this research only focus in Construction Project. Contribution: This research can be use for practical in the project that have critical job need to prepare and control to achive project target, with cost reduction for Rp.10,907,170.03 and project time reduction for 3 days.